Improving the Quality of Research Proposals through the Utilization of Information Technology and Multicompetence - Anak Agung, Putri Suardani; Astawa, I Ketut; Putu Virgananta, Nugraha (Technium Social Sciences Journal, 2025)
This research aims to identify the challenges faced by students when preparing research proposals and to describe the use of information technology and various competencies that can improve the quality of student research proposals. Despite the lack of interest in pursuing a career as a researcher, students are required to complete a final project that requires research skills. Students are trained in writing proposals, data collection, data analysis, and other research related tasks. Data analysis was carried out in a quantitative descriptive manner. The research respondents consisted of 110 Bali State Polytechnic (BSP) students who had taken research methodology courses, selected purposively. The findings show that the use of Google Scholar is rated as excellent, while the utilization of BSP campus repositories, the Publish or Perish web application, Sinta accredited publications, reputable journals, and Mendeley is rated as good. The results also confirmed that proficiency in English and computer skills significantly supported the smooth preparation of research proposals. To improve the quality of student research proposals, attention needs to be paid to six main areas: selection of research topics, provision of more intensive guidance, guarantee of access to international journals and Sinta or Scopus indexed articles, use of plagiarism detection websites, enrichment of teaching materials with comprehensive references, and improvement of lecturers’ ability to explain teaching materials.